Angel patriots : the crash of United Flight 93 and the myth of America - Riley, Alexander (New York University Press, 2015)
""A profound and thought-provoking study, Angel Patriots unveils how, in the wake of 9/11, America mourned much more than the loss of life.""--Daily American